Frontispiece: Polylutidines: Multifunctional Surfaces through Vapor‐Based Polymerization of Substituted Pyridinophanes. Issue 54 (27th September 2017) - Bally‐Le Gall, Florence; Hussal, Christoph; Kramer, Joshua; Cheng, Kenneth; Kumar, Ramya; Eyster, Thomas; Baek, Amy; Trouillet, Vanessa; Nieger, Martin; Bräse, Stefan; Lahann, Joerg
Abstract : A class of functionalized lutidine polymers has been prepared by chemical vapor deposition. The polymers showed a higher adhesion to cells compared to all‐carbon‐based coatings. Furthermore, alkyne‐functionalized polymers were post‐modified by click reactions. This new reactive coating opens new perspectives for the design of new cell biomedical applications. For more information see the Full Paper by S. Bräse, J. Lahann et al. onpage 13342 ff.